After the Whirlwind: Jewish Absence in Postwar Czechoslovakia. (April 2017) - Láníček, Jan
This article analyses absences encountered by Jews in postwar Czechoslovakia. Based on two first-hand accounts (by Leo Herrmann and Joseph Wechsberg), the author offers insights into how Jewish exiles, who visited Czechoslovakia in the first postwar months, perceived the absences caused by the Shoah and by the efforts of postwar societies to create ethnically and linguistically homogeneous countries, without any distinct minority cultures. In postwar Czechoslovakia, the survivors had to cope with the physical absence of those murdered during the war, but also with the loss of multi-culturalism, and ethnic and linguistic diversity of the population. It was expected that the Jews, who decided to stay in postwar Czechoslovakia, would undergo a complete assimilation and would become part of the Czech or Slovak nation. The Jews – a distinct group made absent by the Nazi policies – were further absented from their societies by the postwar reconstruction of their homeland. Although some of the survivors accepted the new rules of the game and attempted to adjust to the new conditions, a majority of those who returned to Czechoslovakia after 1945 soon left the country forever.